Transcriptomic and metabolomic insights on the molecular mechanisms of flower buds in responses to cold stress in two Camellia oleifera cultivars - Wang, Ya-Jun; Wu, Ling-Li; Sun, Min-hong; Li, Ze; Tan, Xiao-Feng; Li, Jian-An (Frontiers in Plant Science, 2023)
Introduction The Camellia oleifera (C. oleifera) cultivars 'Huashuo' (HS) and 'Huaxin' (HX) are new high-yielding and economically valuable cultivars that frequently encounter prolonged cold weather during the flowering period, resulting in decreased yields and quality. The flower buds of HS sometimes fail to open or open incompletely under cold stress, whereas the flower buds of HX exhibit delayed opening but the flowers and fruits rarely drop. Methods In this study, flower buds at the same development stage of two C. oleifera cultivars were used as test materials for a combination of physiological, transcriptomic and metabolomic analyses, to unravel the different cold regulatory mechanisms between two cultivars of C. oleifera. Results and discussion Key differentially expressed genes (DEGs) and differentially expressed metabolites (DEMs) involved in sugar metabolism, phenylpropanoid biosynthesis, and hormone signal transduction were significantly higher in HX than in HS, which is consistent with phenotypic observations from a previous study. The results indicate that the flower buds of HX are less affected by long-term cold stress than those of HS, and that cold resistance in C. oleifera cultivars varies among tissues or organs.This study will provide a basis for molecular markers and molecular breeding of C. oleifera.